New Students' Self-Adjustment at Ar-Risalah Islamic Junior High School: Roles and Supporting Factors - Hasneli, Hasneli; Alfaiz, Alfaiz; Costa, Augusto Da (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this research is to determine teachers’ roles in improving students' self-adjustment and its supporting factors at Ar-Risalah Islamic Junior High School, Padang, Indonesia. This is qualitative descriptive research with data collected from teachers, students, principals, and other school officials through interview, observation, and documentation. The data collected were analyzed using reduction and triangulation processes. The result showed that the teacher had expertise as a motivator to support and trigger the student enthusiasm in adapting and learning new materials at school. Meanwhile, the inhibiting factors of the self-adjustment process were parents that have not been able to let their children go to boarding schools and teachers without psychological backgrounds, because this background are needed for better approach and intervention for children to make them enthusiasm in learning in boarding school